2006
DOI: 10.1016/j.jastp.2005.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of CRISTA mesopause region temperatures for the intercalibration of ground-based instruments

Abstract: Most available ground-based (GB) techniques for measuring temperatures in the upper mesosphere to lower thermosphere (or mesopause region) have systematic errors that are comparable to those of orbiting instruments. Determining these unknown biasses would normally require colocated observations that are only seldom feasible. Satellite measurements can be used as a ''transfer standard'' between GB observations that are not colocated. In this context, even with a reproducible or known bias in the satellite data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The ground-based temperatures were 4-5 K higher than SABER values, similar to earlier reports (von Savigny et al, 2004;Oberheide et al, 2006;Scheer et al, 2006;López-González et al, 2007;Mulligan and Lowe, 2008). As T OH derived from Meinel band line intensities strongly depend on the choice of transition probabilities (French et al, 2000), T OH were also derived using the transition probabilities given by Mies (1974), Turnbull and Lowe (1989) and Goldman (1998); however, the mean difference between T OH and SABER measurements increased from 3 to 15 K with their use.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The ground-based temperatures were 4-5 K higher than SABER values, similar to earlier reports (von Savigny et al, 2004;Oberheide et al, 2006;Scheer et al, 2006;López-González et al, 2007;Mulligan and Lowe, 2008). As T OH derived from Meinel band line intensities strongly depend on the choice of transition probabilities (French et al, 2000), T OH were also derived using the transition probabilities given by Mies (1974), Turnbull and Lowe (1989) and Goldman (1998); however, the mean difference between T OH and SABER measurements increased from 3 to 15 K with their use.…”
Section: Resultssupporting
confidence: 90%
“…A difference of 7-12 K between T OH and T 2.0 was observed in a large number of remaining coincidences. Scheer et al (2006) reported the difference of 0.2-11.5 K between the ground-based T OH and CRISTA temperatures. As a trial, OH-equivalent temperatures were calculated using an intermediate weighing function, viz.…”
Section: Oh-equivalent Temperatures From Saber Kinetic Temperature Prmentioning
confidence: 99%
See 2 more Smart Citations
“… Nominal peak emission heights are from Baker et al [] for OH, McDade [] for O 2 , and Scheer et al [] for OI.…”
Section: Introductionmentioning
confidence: 99%